Issues, Challenges, and Progress of Autonomous Robotic Platoons - Gunagwera, Alex; Zengin, Aydın Tarık (IGI Global, 2022)
The number of vehicles on the roads worldwide grows annually. With the increase in the population of on-road vehicles comes the increase in traffic-related problems such as emissions, traffic accidents, traffic jams, and increased fuel consumption, to mention but a few. The field of robotics presents the autonomous robotic platooning concept, which presents a very promising future for the transportation industry in general and intelligent transportation industry, in particular. With autonomous platooning, efficient road usage, reduced fuel consumption and emission are possible. This promising field, however, faces issues and challenges barring the deployment of autonomous platoons. In this chapter, the authors introduce the user to the concept of autonomous platooning, present the current state-of-the-art of autonomous robotic platoons and issues that they still face, and ultimately, discuss their progress and future trends.
Design and Control Advances in Robotics / Editör:Mohamed Arezk Mellal -- IGI Global -- ISBN:978-166845383-4, 978-166845381-0 -- 2022.